Rancangan Strategi dalam Menanggulangi Risiko pada Proses Pengadaan di PT. Asahimas Chemical dengan Menerapkan Konsep "House of Risk" - Putra, Resha Widya Permana; Widjanarko, Alain (Journal of Emerging Business Management and Entrepreneurship Studies, 2024)
The purpose of this research about risk management in the supply chain is to identify potential risks that occur and the causes of the risks and to obtain a correlation between the causes of the risks and the risk events in the company. The research method using the HOR method, from the results obtained, there are seven main risks, namely the selection of land and sea transportation. The selection of land and sea transportation is not standard and has many problems (delays), shortages in supply capacity, unclear PR specifications, QA/QC processes are not followed, ship arrival is not on time, the high overturn of employees, and a significant increase in demand. Significant increase in demand. The conclusion obtained 7 (seven) significant preventive measures, including Among them are building Using tracking technology and logistics management to monitor the transportation movement of transportation equipment in real-time, identifying areas or stages of areas or production stages that can be improved to overcome shortcomings, implementing a review process involving review process that involves competent parties, periodic internal audits to evaluate compliance with QA procedures. Periodically to evaluate compliance with QA/QC procedures and insert punctuality clauses in contracts. Timeliness clauses in contracts with shipping companies or logistics service providers consider policies for work-life balance to reduce fatigue and stress and proactively increase production capacity.